Bangngi Korongtigi: Girlfriend's Night Ritual in the Wedding Tradition of the Sayyid Community in Cikoang - Wandhini, Nur Annisa; Najamuddin; Ahmadin (Formosa Journal of Sustainable Research, 2025)
This study aims to determine the background of the implementation of the Bangngi Korongtigi tradition in Cikoang Village, Manggarabombang District, Takalar Regency, the dynamics of the Bangngi Korongtigi Tradition, and the impact of the Bangngi Korongtigi Tradition on local communities. This research is a historical research method using four stages of work, namely heuristics, criticism, interpretation, and historiography. Data collection used observation, interview, and documentation techniques. The results showed that the Bangngi Korongtigi tradition in the marriage of the sayye community in Cikoang village has not changed significantly. Although the Bangngi Korongtigi ceremony in Cikoang has entered the age of modernization, the implementation of Bangngi Korongtigi of course changes that occur during the second phase cannot be avoided. The impetus for change comes not only from internal factors, but also from external factors. Nevertheless, the development of the Bangngi Korongtigi tradition continues to look forward. This study concludes that the Bangngi Korongtigi tradition has not changed in the implementation process. Changes only occur in the use of materials, namely grain, cotton trees, and offerings